1991
DOI: 10.1111/j.1365-2761.1991.tb00608.x
|View full text |Cite
|
Sign up to set email alerts
|

Herpesvirus cyprini: lethality and oncogenicity

Abstract: Cyprinid herpesvirus 1 (CHV) or Herpesvirus cyprini was virulent for carp, Cyprinus carpio L.. fry following lh immersion in water at 20X. Cumulative mortality for carp fry was 86-97% in 2-week-old eommon carp, 20% in 4-week-oId faney carp, and 0% in both 8week-old common and fancy carp. The virus did not produce mortality in fry of crucian carp, grass carp or other eyprinids. It was also oncogenic in earp. inducing papillomas to the extent of 55% among both common and fancy earp fry. The neoplasms appeared 5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 7 publications
(2 reference statements)
0
53
0
Order By: Relevance
“…CHV is responsible for both skin tumors or carp pox lesions in adult carp and dissemination form of the disease in juvenile carp. It was found that CHV cause lethal and systemic infections not only in common carp but in any cyprinid including koi carps less than two month in age (Sano et al, 1991, Calle et al, 1999.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…CHV is responsible for both skin tumors or carp pox lesions in adult carp and dissemination form of the disease in juvenile carp. It was found that CHV cause lethal and systemic infections not only in common carp but in any cyprinid including koi carps less than two month in age (Sano et al, 1991, Calle et al, 1999.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…Such papillomas coalesce as they spread over the surface of carp as white plaques, and develop focal exophytic masses (Wildgoose, 1992). These papillomas are caused by Herpesvirus cyprini (also cyprinid herpesvirus 1, CHV) (Sano et al, 1991), regress in warm summers or when held above 20°C (Sano et al, 1993b), and persist below 15°C (Sano et al, 1993a). Viruses have also been associated with papillary epidermal plaques in other fish species (Wolf, 1988), such as walleye, in which a retroviral etiology is suspected (LaPierre et al, 1998).…”
Section: Beckwith Et Almentioning
confidence: 99%
“…The causative agent, carp pox herpesvirus or cyprinid herpesvirus 1 (CyHV-1), was identified as a virus belonging to the herpes group in the 1950s (Schubert 1966) and first isolated a few decades later (Sano et al 1985). Although mortalities can be evoked in carp fry (Sano et al 1991), in general the effect of the disease on its host is limited and is primarily a problem in the cultivation of ornamental carp because of the focal epidermal hyperplasia. On the other hand, koi herpesvirus disease (KHVD) is a recently emerging and lethal disease of koi and common carp, with cyprinid herpesvirus 3 (CyHV-3) as the causative agent (Waltzek et al 2005(Waltzek et al , 2009.…”
Section: Introductionmentioning
confidence: 99%